Forced swim test induces divergent global transcriptomic alterations in the hippocampus of high versus low novelty-seeker rats - Pitychoutis, P M; Sanoudou, D.; Papandreou, M.; Nasias, D.; Kouskou, M.; Tomlinson, C. R.; Tsonis, P A; Papadopoulou-Daifoti, Z. (Hum GenomicsHum GenomicsHum Genomics, 2014)
BACKGROUND: Many neuropsychiatric disorders, including stress-related mood disorders, are complex multi-parametric syndromes. Susceptibility to stress and depression is individually different. The best animal model of individual differences that can be used to study the neurobiology of affect regards spontaneous reactions to novelty. Experimentally, when naive rats are exposed to the stress of a novel environment, they display a highly variable exploratory activity and are classified as high or low responders (HR or LR, respectively). Importantly, HR and LR rats do not seem to exhibit a substantial differentiation in relation to their 'depressive-like' status in the forced swim test (FST), a widely used animal model of 'behavioral despair'. In the present study, we investigated whether FST exposure would be accompanied by phenotype-dependent differences in hippocampal gene expression in HR and LR rats. RESULTS: HR and LR rats present a distinct behavioral pattern in the pre-test session but develop comparable depressive-like status in the second FST session. At 24 h following the second FST session, HR and LR rats (stressed and unstressed controls) were sacrificed and hippocampal samples were independently analyzed on whole rat genome Illumina arrays. Functional analysis into pathways and networks was performed using Ingenuity Pathway Analysis (IPA) software. Notably, hippocampal gene expression signatures between HR and LR rats were markedly divergent, despite their comparable depressive-like status in the FST. These molecular differences are reflected in both the extent of transcriptional remodeling (number of significantly changed genes) and the types of molecular pathways affected following FST exposure. A markedly higher number of genes (i.e., 2.28-fold) were statistically significantly changed following FST in LR rats, as compared to their HR counterparts. Notably, genes associated with neurogenesis and synaptic plasticity were induced in the hippocampus of LR rats in response to FST, whereas in HR rats, FST induced pathways directly or indirectly associated with induction of apoptotic mechanisms. CONCLUSIONS: The markedly divergent gene expression signatures exposed herein support the notion that the hippocampus of HR and LR rats undergoes distinct transcriptional remodeling in response to the same stress regimen, thus yielding a different FST-related 'endophenotype', despite the seemingly similar depressive-like phenotype.
Pitychoutis, Pothitos MSanoudou, DespinaPapandreou, MargaritaNasias, DimitrisKouskou, MariannaTomlinson, Craig RTsonis, Panagiotis APapadopoulou-Daifoti, ZetaengEY16707/EY/NEI NIH HHS/Research Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov'tEngland2014/02/27 06:00Hum Genomics. 2014 Feb 25;8:4. doi: 10.1186/1479-7364-8-4.
Keywords: *Exploratory Behavior; *Gene Expression Profiling; Animals; Depression/*metabolism; Gene Expression/*genetics; Hippocampus/*metabolism/physiology; Physical Exertion; Rats; Swimming